A Reliable and High-Performance Distributed Storage System for P2P-VoD Service - Jing Zhao; Hongbo Wang; Jiankang Dong; Shiduan Cheng (2012 IEEE International Conference on Cluster Computing, 2012)
Online video service has become one of the main Internet applications, especially video-on-demand (VoD). Most VoD systems are based on P2P technology currently. As the number of users and media files grows rapidly on demand, the storage capacity of source media files becomes limited. Besides, the system performance and user experience drops obviously when online users do not share the same data. In this paper, we present a reliable and high-performance distributed storage system for P2P-VoD service based on Hadoop Distribute File System (HDFS). The reliability and scalability of the system are proved through experiments. The results also verify that the data response time and server utilizations get improved, which means the system gets a better performance.